Classical archaeology - Alcock, Susan E.; Osborne, Robin 1957- (Blackwell studies in global archaeology, 2012)
"The fully revised second edition of this successful volume includes updates on the latest archaeological research in all chapters, and two new essays on Greek and Roman art. It retains its unique, paired essay format, as well as key contributions from leading archaeologists and historians of the classical world. Second edition is updated and revised throughout, showcasing the latest research and fresh theoretical approaches in classical archaeology Includes brand new essays on ancient Greek and Roman art in a modern context Designed to encourage critical thinking about the interpretation of ancient material culture and the role of modern perceptions in shaping the study of art and archaeology Features paired essays - one covering the Greek world, the other, the Roman - to stimulate a dialogue not only between the two ancient cultures, but between scholars from different historiographic and methodological traditions Includes maps, chronologies, diagrams, photographs, and short editorial introductions to each chapter "